Options for volatile markets : managing volatility and protecting against catastrophic risk - Lehman, Richard, 1948-; McMillan, L. G. (Lawrence G.); Lehman, Richard, 1948= (Hoboken, NJ : John Wiley and Sons, 2011)
'Traditional thinking about investment has been thrown on its head in the wake of the financial crisis. Many investors no longer accept the idea that diversification reduces risk and the stock market provides the best long-term returns. With global markets increasingly interlinked, markets tend to move in concert, reducing the benefits of diversification. And given the gravity of today's economic problems, many question whether the stock market will soon continue its inexorable march higher. In Options in Volatile Markets, Lehman and McMillan provide investors with strategies to generate double-digit returns and to protect against market crashes. The new edition discusses the changing investment environment; explains how to use options with ETFs; and shows how build'catastrophic' protection into a portfolio. While the core strategy remains covered call writing - selling a call option on a stock the investor already owns - the authors discuss other strategies to capitalize on high-flying stocks. Most importantly, for investors looking for high returns but fearful that the market might crash, the authors discuss low-cost options strategies that effectively provide insurance for a portfolio'--
Rev. ed., previously published under title: New insights on covered call writing by Bloomberg Press in 2003.
Includes index.
Keywords: Investments